Behavioral and transcriptomic changes in butenolide treated larvae of the cosmopolitan fouling bryozoan Bugulina (Bugula) neritina - Liang, Jin-You; Cheng, Yi-Fan; Huang, Xiao-Lin; Xu, Ying; Wong, Yue Him; Zhang, Yu (Frontiers in Marine Science, 2022)
The arborescent bryozoan Bugulina neritina is a cosmopolitan fouling species in sub-tropical to sub-temperate waters. The butenolide compound 5-octylfuran-2(5H)-one (hereafter named butenolide) reportedly inhibits larval settlement of B. neritina, but its effect on the larval behavioral and transcriptomic responses remained unclear. We report that 10 μg mL-1 or higher concentration of butenolide and/or prolonged treatment (10 h or longer) resulted in significant increase in larval mortality and prominent spiral larval swimming behavior. The transcriptomic analyses not only revealed up-regulation of typical stress-related protein genes in response to 10 mg mL-1 butenolide treatment, but also indicated up-regulation of mucin, synaptic genes and nitric oxide signaling genes. In addition, the expression of developmental genes and lipid biosynthesis genes were also affected. Overall, our larval behavior and transcriptome analyses reflected the impact of butenolide on the metabolism, neuronal and molecular signaling in B. neritina larvae.